Pengaruh Pemberian Teh Bevuzingiber (Beta vulgaris dan Zinger officinale) pada Pasien Hipertensi Tingkat I di Wilayah Kerja UPT Puskesmas Way Kandis Tahun 2025 - Janah , Widya Miftakhul; Astuti, Dewi Woro; Hervidea, Radella (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Hypertension is a major global health issue characterized by a persistent increase in arterial blood pressure, leading to severe complications. Stage I hypertension is defined as systolic blood pressure of 140-159 mmHg and diastolic pressure of 90-99 mmHg. The high prevalence of hypertension in the work area of UPT Puskesmas Way Kandis necessitates effective and accessible non-pharmacological interventions, such as the use of local ingredients like beetroot (Beta vulgaris) and ginger (Zingiber officinale). Objective: This study aimed to analyze the effect of consuming Bevuzingiber tea (a combination of Beta vulgaris and Zingiber officinale) on reducing blood pressure in patients with stage I hypertension. Methods: This study used a quantitative quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 36 stage I hypertension patients selected through purposive sampling. They were divided into two groups: an intervention group (n=18) given Bevuzingiber tea and a control group (n=18) given antihypertensive medication. The intervention was conducted for 7 days. Blood pressure was measured before and after the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: The results showed a significant reduction in blood pressure in the intervention group. The average systolic blood pressure decreased from 152.00 mmHg to 113.89 mmHg, and diastolic pressure decreased from 91.50 mmHg to 74.17 mmHg. Statistical analysis confirmed a significant difference with a p-value of 0.000 (<0.05). The intervention group also showed more consistent reductions compared to the control group. Conclusion: Bevuzingiber tea is effective in reducing blood pressure in patients with stage I hypertension and can be recommended as a complementary non-pharmacological therapy. It is suggested that future researchers focus on patients under 65 years of age and directly observe respondents' activities and other factors influencing blood pressure.